Preparation of fortified biscuits from a mixture of cereals, legumes and tubers. Chachapoyas, Amazonas Region - Auquiñivin Silva, Erick Aldo (2016)
The main objective of this research was to encourage innovation of products from the area, and thus exploit the potential of the properties that show these products and the importance of nutrition use in infant feeding. The specific objective of this research was to enrich nutritionally cookies and flavor, to meet this objective partly replaced wheat flour for local products such as Pajuro and Oca. The stages of the process flow were as follows: The formulation of ingredients, mixing, kneading, forming, baking and cooling. Total protein content, moisture and ash made of different cookies were evaluated. Likewise, sensory analysis where 31 children 10 years old participated was performed pre-selected and trained, who evaluated the taste, by the hedonic technique. Where seven treatment was the result of this investigation.